Nutritional evaluation of soybean meal after fermentation with two fish gut bacterial strains, Bacillus cereus LRF5 and Staphylococcus caprae CCF2 in formulated diets for Labeo rohita fingerlings - Dan, Suhas Kumar; Banerjee, Goutam; Nandi, Ankita; Ray, Arun Kumar (Journal of Fisheries, 2017)
Twelve isonitrogenous (35 % crude protein) and isocaloric (18.0 kJ/g) diets were formulated incorporating raw and fermented soybean meal (SBM) at 15%, 30%, 45% and 60% levels by weight. Two phytase-producing bacterial strains, Bacillus cereus LRF5 and Staphylococcus caprae CCF2 isolated from the gut of adult Labeo rohita and Catla catla, respectively were used for fermentation of SBM. Fermentation of SBM was effective in reducing the anti-nutritional factors, trypsin inhibitor and phytic acid and enhancing protein, lipid and mineral concentration. The response of L. rohita, fingerlings (initial weight 3.33±0.07 g) fed the experimental diets for 100 days was compared with fish fed a fish meal based diet. In terms of growth, feed conversion ratio and protein efficiency ratio, diet S7 containing 45% SBM fermented with B. cereus LRF5 resulted in a significantly (P<0.05) better performance of fish. The overall performance of L. rohita fed fermented SBM incorporated diets was better in comparison to those fed raw SBM incorporated diets. The apparent digestibility of nutrients and minerals was significantly (P<0.05) higher in fish fed diet S7. The maximum deposition of protein in the carcass was recorded in fish fed diet S7. Diets containing fermented SBM reduced fecal P levels.